Studi Kasus terhadap Putusan Peninjauan Kembali Nomor 109 PK/Pdt/2022 dalam Kasus Dago Elos Ditinjau dari Kitab Undang-Undang Hukum Perdata dan Peraturan Terkait - Amanda Khoirunnisa Salsabila; Dr. Etty Haryati Djukardi, S.H., M.H., CN.; Dr. Hj. Yani Pujiwati, S.H., M.H. (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2024)
A person or legal entity that acquires rights to land must register their land ownership. However, land ownership can also lead to disputes, such as the dispute over former eigendom verponding land numbers 3740, 3741, and 3742 in Dago Elos. The Defendants have occupied the land for years without issues, and some have certificates of land ownership or building rights. In the verdict of Judicial Review Case Number 109 PK/Pdt/2022, the Defendants' actions in occupying the disputed land were deemed illegal. Therefore, the author is interested in analyzing whether the Defendants' actions meet the elements of illegal actions according to Article 1365 of the Civil Code and related regulations, and to what extent the Defendants are protected by the verdict. The research was conducted using a normative juridical method, with literature review generating descriptive notes and data, and utilizing a statutory approach. The results show that the Defendants' actions in occupying the disputed land do not constitute illegal actions under Article 1365 of the Civil Code due to the lack of elements. No legal protection can be provided because the verdict is final. The judge did not provide legal reasoning based on the juridical alignment between legal facts, evidence, and the legal basis of statutory regulations.